The futures of the Singapore association of social workers: an analysis using CLA and the "Futures Triangle". Issue 4 (5th August 2014) - Fan, Gilbert; Nee Wey Khng, Joan
Abstract : Purpose: – This paper aims to study the future of the Singapore association of social workers using causal layered analysis (CLA) and the Futures Triangle. In today's rapidly changing world, professional associations have to re-evaluate their roles to remain relevant. This paper presents an analysis of findings from a study on the level of alliance of social workers with their professional association. By critically examining underlying issues beneath common beliefs held by social workers that impede, promote or sustain change with their professional association, we can gain a deeper understanding into their level of alliance with their association. Insights toward current issues faced by the association as well as its alternative and preferred futures could be illuminated. Design/methodology/approach: – Inayatullah's "Futures Triangle" was used to deepen the findings of the study on the level of alliance of social workers with their professional association from the lens of CLA (Inayatullah, 2004). The study employed interviews with 27 social workers in Singapore, selected through purposive sampling. Findings: – Alternative scenarios and preferred futures of the Singapore Association of Social Workers (SASW) that were postulated from the interviews reinforce a need for more targeted recruitment campaigns. It also calls for regionalization and globalization of SASW to maximize its potentials. Originality/value: – The paper suggests how a social work association might be able to reposition its role in relation to its stakeholders to promote and sustain itself. SASW could do so through positioning itself as the "National Geographic" beacon for social workers in Singapore to reach out to the world.